Biology and Pathology of Perineuronal Satellite Cells in Sensory Ganglia - Pannese, Ennio (Advances in Anatomy, Embryology and Cell Biology,, 2018)
This volume provides a comprehensive and updated review of perineuronal satellite cells in sensory ganglia. For a long time since their discovery by Valentin in the first half of the 19th century these cells received only modest attention. However, some years ago research findings suggested that satellite cells play a role in the development and maintenance of neuropathic pain. As a result, satellite cells are now considered as possible targets for neuropathic pain treatment. Thus, interest in satellite cells has burgeoned. The review is based on the author's own work as well as on his critical evaluation and systematic arrangement of data scattered through a large number of research papers. The following aspects of perineuronal satellite cells are covered: Shape and structure; molecular characteristics; origin and development; biological and functional properties; relationships with the ganglion sensory neuron; age-related changes; roles under physiological conditions; reactions to experimental and pathological conditions; role in neuropathic pain.